International transmission of economic shocks: The case of mixed exchange rates in a three-country world - Nikolaus K. A. Läufer; Srinivasa Sundararajan (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
The international transmission of economic disturbances is analysed in a three-country world where two countries have no macroeconomic impact on a third country but are large enough to influence each other under a system of mixed exchange rates - a system that combines the fixed exchange rates (FERs) among two EC member countries (Germany and France) and the flexible exchange rates (FLERs) towards a third country, the rest of the world (USA). We find that a positive Output demand shock originating in Germany or France has a positive effect on domestic output, but, due to a new third country effect, is likely to produce a contractionary impact on foreign output (negative transmission) while the total effect on the world economy is expansionary. Money supply shocks in either Germany or France have identical effects on the output of the two countries. The FLER component of the MER regime serves as an important tool for dampening the impact of US shocks on the output of the EC.
Keywords: 330